2017
DOI: 10.5586/asbp.3551
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase is involved in regulation of gene expression and ROS overproduction in soybean (Glycine max L.) seedlings exposed to cadmium

Abstract: Cadmium-induced oxidative burst is partially mediated by NADPH oxidase. The aim of the present research was to evaluate the role of NADPH oxidase in soybeans’ response to short-term cadmium stress. The application of an NADPH oxidase inhibitor, diphenyleneiodonium chloride (DPI), affected expression of two Cd-inducible genes, encoding DOF1 and MYBZ2 transcription factors. This effect was observed after 3 h of treatment. Interestingly, Cd-dependent increases in NADPH oxidase activity occurred only after a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…Various biotic and abiotic stresses lead to the production of different ROS such as O 2 − , 1 O 2 , HO • , and H 2 O 2 . Unlike atmospheric oxygen, these molecules are highly reactive, very toxic to the cell, and cause significant damage to various cell structures, membranes, nucleic acids, proteins, enzymes, and lipids [5,24]. As a consequence, plant defense systems are induced which can be classified into enzymatic and non-enzymatic [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various biotic and abiotic stresses lead to the production of different ROS such as O 2 − , 1 O 2 , HO • , and H 2 O 2 . Unlike atmospheric oxygen, these molecules are highly reactive, very toxic to the cell, and cause significant damage to various cell structures, membranes, nucleic acids, proteins, enzymes, and lipids [5,24]. As a consequence, plant defense systems are induced which can be classified into enzymatic and non-enzymatic [25].…”
Section: Discussionmentioning
confidence: 99%
“…The activities of the tested antioxidant enzymes were induced in the treated seedling of P. sativum with either Cd or Ni (Figure 3 and Figure 4). A literature review has shown that NADH-oxidase activity was induced due to the induction of various ROS such as O 2 − and H 2 O 2 following biotic and abiotic stresses [24]. The SOD is considered as the first enzyme that triggered under oxidative stress, where it acts directly on superoxide radicals (O 2 − ) which is the precursor of the other ROS [35].…”
Section: Discussionmentioning
confidence: 99%
“…Also our earlier research showed that ROS signal in soybean seedlings exposed to Cd differs in time. The activity of NADPH oxidase modulated expression of signaling associated genes after 3 h of metal treatment, while significant ROS accumulation and lipid peroxidation were noted only after 24 h ( Chmielowska-BąK et al, 2017 ). Apparently, the role of ROS in plant cells is temporal, species, and spatial specific ( Miller et al, 2008 ; Cuypers et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of present study was examination of the influence of Cd in two concentrations (10 and 25 mgl -1 ) on the intensity of oxidative stress and frequency of RNA oxidation-dependent modifications – 8-OHG and AP-sites. Our previous research showed that in the earliest period of Cd stress (3 h), ROS are engaged in the regulation of gene expression, while strong accumulation of O 2 - and H 2 O 2 has been marked after 24 h ( Chmielowska-BąK et al, 2017 ). Therefore, these two time points, 3 and 24 h, were applied in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was partly supported by Chmielowska et al [ 109 ] when the authors reviewed cadmium sensing in plants. Furthermore, Chmielowska et al [ 110 ] showed that NADPH oxidase activity only occurred after the periods of 6 and 24 h after cadmium stress. In the same study the authors showed that a MAPK cascade gene was activated after 3 h. This could point to MAPK isoform specific activation by superoxide, or that the activation of MAPK can occur independently of superoxide, as well as a time-dependent activation of MAPK by superoxide.…”
Section: The Role Of Other Wall-associated Proteins In Heavy Metalmentioning
confidence: 99%